AVALIAÇÃO MORFOLÓGICA E PRODUTIVA DE AMENDOIM PRODUZIDO POR PEQUENOS AGRICULTORES DO RECÔNCAVO DA BAHIA - ADEMIR TRINDADE ALMEIDA; CLOVIS PEREIRA PEIXOTO; LUIZ FERNANDO MELGAÇO BLOISI; JAMILE DA SILVA OLIVERIA; VIVIANE GUZZO DE CARLI POELKING (Revista Caatinga, 2014)
The objective of this study was evaluate the morphological variability and existing production between peanut genotypes collected from small farmers in seven counties in Recôncavo of Bahia, in addition to selecting the most promising materials. Peanut seeds (60 genotypes) were collected along the ethnobotanical survey. Each genotype was collected from a zoned farmer in the study area. Experimental design was a randomized block with four replications. For morphological analysis of growth characteristics were evaluated: main stem height, number of leaves and number of branches also have assessed them components of plant production and productivity, which were evaluated: the volume of fresh and dried vegetable, fresh vegetable pasta and dried, the diameter and length of vegetables, total number of vegetables, total number of grains and the weight of 100 grains. The data were subjected to analysis of variance and means were compared by the Scott- Knott test at 5% probability. Although not shown variability the vegetative morphological characteristics, yield characteristics are indicative of the existence of variability, and why it has become possible to preselect seven peanut genotypes collected from farmers in the Recôncavo of Bahia, which may be considered important descriptors for the distinction of superior genotypes.